Computer Virus and Trends - Tutut Handayani; Soenarto Usna,Drs.MMSI (Jurnal Sistem Informasi, 2004)
Since its appearance the first time in the  mid-1980s, computer virus has invited various controversies that still lasts  to this day. Along with the development of computer systems technology, viruses komputerpun find new ways to spread itself through a variety of existing communications media. This paper discusses about some things related to computer viruses, namely: the definition and history of computer viruses; the basics of computer viruses; state of computer viruses at this time; and prediction of computer virus that emerged in the future.